Two new species of the genus Siro Latreille, 1796 (Opiliones, Cyphophthalmi, Sironidae) in the European fauna - Karaman, Ivo; Lienhard, Andrea; Niklos, Kathrin; Raspotnig, Guenther (European Journal of Taxonomy, 2022)
Two new opilionid species from suborder Cyphophthalmi, family Sironidae, Siro franzi Karaman & Raspotnig sp. nov. and Siro ozimeci Karaman sp. nov., from Austria and Croatia respectively, are described and illustrated. Both species show a close relation to two other relict sironid species from the southern and eastern parts of the Alps, Siro valleorum and Siro crassus. All four species are treated here as a monophyletic, alpine group of genus Siro, opposed to the remaining two European sironids, S. rubens and S. carpaticus (palaeoeuropean Siro group). The history of the alpine Siro group parallels the history of a part of the dynamic European archipelago in the Mediterranean Tethys area, which became a part of the Alpine orogeny. Diversification of the alpine Siro group is the result of the orogenic evolution of the Alps, linked to the Austroalpine and South Alpine tectonic units.